THU0017 ATTEMPTS TO LINK EXONIC GENE POLYMORPHISMS TO SYSTEMIC LUPUS ERYTHEMATOSUS (SLE)-ASSOCIATED PROTEIN MODIFIED FUNCTIONALITY: A STRUCTURAL BIOLOGY APPROACH. (2nd June 2020) - Eliopoulos, E.; Goulielmos, G.; Matalliotakis, M.; Vlachakis, D.; Niewold, T.; Zervou, M.
Abstract : Background: Gene association studies and genome wide association studies (GWAS) have played a primary role in depicting genetic contributions to systemic lupus erythematosus (SLE) development, while accommodating the exonic polymorphisms on the protein structure level, when available, enhances our understanding of protein function modification or depletion. Linking human genetics with therapeutic targets requires the biological function of the causal gene and variant to be known. Objectives: To investigate recently identified SLE-associated functional gene polymorphisms, such as PARP1, ITGAM, TNFAIP3, NCF1, PON1, IFIH1, SH2B3 and TYK2 [1-4] by correlation to protein structure and function. Methods: Three-dimensional (3D) homology modeling and molecular mechanics/dynamics studies were applied for the localization of the polymorphisms under study on the respective proteins. The mutants were constructed using molecular modeling with the program Maestro (Schrodinger, LLC), which was also used to analyze the conformational changes caused by the mutation. All figures depicting 3D models were created using the molecular graphics program PyMOL V.2.2 [5]. Results: Modeling revealed that rs1136410 SNP encodes the less common polymorphism Val762Ala on PARP1 that reduces enzymatic activity of Poly(ADP-ribose) polymerase 1 (Figure 1 ), ITGAM polymorphism rs1143679 (Arg77His) on Integrin alpha M, component of the macrophage-1 antigen complex affects protein surface recognition, TNFAIP3 rs2230926 polymorphism encodes Cys instead of Phe at residue 127 of the ubiquitin editing A20 protein, while rs201802880 polymorphism of the neutrophil cytosolic factor 1 ( NCF1 ) gene modifies the function of the cytosolic subunit of neutrophil NADPH oxidase with the mutation Arg90His. PON1 is involved in the oxidative stress process that cause tissue damage observed in SLE and anti-phospholipid syndrome (APS). The PON1 Gln192Arg mutation (rs662 SNP) affects shape and recognition of the ligand recognition site as part of the evolutionary process, while IFIH1 (rs35667974) helicase C domain1 mutant I923V is located on an essential RNA beta loop interacting directly with the nucleic acid (Figure 2 ). Finally, the rs3184504 SNP of SH2B3 gene generates mutant Arg262Trp on SH2 adapter protein 3, acting as a signaling pathway involved in autoimmune disorders, while in TYK2 gene, one of the Janus kinases, the rs35018800 producing mutant Ala928Val modifies the ADP binding site. Conclusion: Based on several examples, we have tried to define a rational link from SLE-associated gene polymorphisms to structure and to modified function, including metagenomic analysis of SNPs, protein crystallography, protein molecular modeling, molecular mechanics and dynamics. Locating, shaping and understanding the target protein interaction interface plays a decisive role in most cases and provides clues for further pharmacological or medical actions [6]. References: [1]Hur JW et al (2006). Rheumatology 45:711-7 [2]Maiti AK et al (2014). Hum Mol Genet 23:4161-76 [3]Shimane K et al (2010). Arthritis Rheum. 62:574-9 [4]Linge P et al (2019). Ann Rheum Dis. 2019 Nov 8. pii: annrheumdis-2019-215820 [5]Schrödinger LLC: The PyMOL Molecular Graphics System 2016 version 2.2. Available from: pymol.org/2/support.html [6]Plenge RM et al (2013). Nat Rev Drug Discov 12:581–94 Disclosure of Interests: None declared